A case study of the investment yields of high street banks. Issue 5 (1st August 2016) - Lam, Terence Y.M.; Tipping, Malvern
Abstract : Purpose: – Sale-and-leaseback has become an increasingly common approach during the last two decades in the investment of high street banks (banking-halls) in the UK. One measure commonly used in making property investment decisions is the all risks yield (ARY) which is associated with the level of rental income. Investors and their advisors need to know which factors are likely to result in the highest ARY when assembling investment portfolios of such properties. The purpose of this paper is to identify those yield influences. Design/methodology/approach: – A qualitative multiple-case study was adopted. A literature review generated a hypothesis which was tested by a qualitative study, based upon semi-structured interviews and a questionnaire, to establish the influencing factors. Expert interviews were held with the heads of those three major auction-houses dealing with auctions of all retail bank premises in the Great Britain market, whilst the questionnaire survey involved investment professionals from within the auction-houses. Findings: – The study confirmed that the four factors influencing yields and investors' decision-making when purchasing retail banking premises were tenant banking company (brand names), regional location (north and south super-regions), lot size (hammer price), and tenure (freehold or leasehold). Research limitations/implications: – This investigation focuses on Great Britain's geographical and political area which includes England, Scotland and Wales, but excludes Northern Ireland. This research focuses on banking-halls as a sub-class of retail property investment. The findings form a baseline upon which further research can be conducted on other sub-types of retail property such as high street shops and retail parks. The results will also underpin the development of a quantitative yield predictive model based on regression analysis. Practical implications: – To maximize the returns on property investments, investors and their professional advisors can use those factors having the greatest influence on yields to make informed investment decisions for the building of property portfolios. Originality/value: – As a sub-sector, bank premises do not necessarily correlate to the generic retail sector. This research consolidates the broad systematic drivers of retail yields into specific factors influencing the ARY of banking-halls. The findings provide better understanding of an active but sparsely analysed sub-market of banking hall investments, and by so-doing help investors to maximize their investment returns.